A study on the visual reaction times of hearing-impaired adolescents - Sözen, H.; Ari, E. (International Journal of Applied Exercise Physiology, 2020)
The aim of this study was to examine visual reaction time values of adolescents according to gender, hearing impairment and dealing with sports situation. The 78-hearing impaired and 78 normal hearing students joined to study voluntarily. The visual reaction time values of dominant and non-dominant hands were measured by reaction measurement device in laboratory. According to statistical analyze results, it was determined that there was significantly difference between visual reaction time values of students in terms of gender and hearing impairment situation and male and hearing impaired students had faster visual reaction time values compared to female and normal hearing students (p<0.05). It was found that the visual reaction time values of students were not differentiated according to situation of dealing with sports of students and sedentary and athlete students had similar visual reaction time values. As conclusion, it might be said that the reason of faster visual reaction time values of hearing-impaired students compared to normal hearing students was to be used of visual signs frequently by hearing impaired students for facilitating their daily life activities and eliminating disadvantages of hearing impairment.